The Parent's socioeconomic status influence and automotive learning achievement towards their interest for continue to university of second grade student of automotive mechanical engineering SMK Batur Jaya 1 Ceper, Regenci Klaten in academic year of 2013/2014 - Lingga Arti Saputra; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research is for find out the Parent's socioeconomic status influence and automotive learning achievement towards their interest for continue to university of second grade student of automotive mechanical engineering SMK Batur Jaya 1 Ceper, Regenci Klaten in academic year of 2013/2014.Hypothesis in this research are (1) there are positive influence and significant between parent’s socioeconomic status and learning achievement towards their interest for continue to university, (2) there are positive influence and significant between parent’s socioeconomic status and learning achievement towards their interest for continue to university, (3) there are positive influence and significant between parent’s socioeconomic status and learning achievement towards their interest for continue to university. This research is an ex-post faxto research with population in this research is as much as 145 students and number of samples are 119 by used Harry King’s fungsion . Data collecting techniques by using questionnaire and documentation. Data analysis techniques in this research are use partial correlation analysis and double regression. Before doing hypothesis test, firstly doing normality test, linearity test, multi-correlation test.The result of this research shows there are positive influence and significant between parent’s socioeconomic status and learning achievement towards their interest for continue to university, parent’s socioeconomic status shows positive influence and significant towards their interest for continue to university, mechanical automotive achievement shows positive influence and significant towards their interest for continue to university. Based on the research and hypothesis test that has been done prove that more higher parent’s socioeconomic status and automotive learning achievement, the interest of continue to the university more higher too.